Coinjection with TLR2 Agonist Pam3CSK4 Reduces the Pathology of Leishmanization in Mice - Huang, Lu; Hinchman, Meleana; Mendez, Susana (PLOS Neglected Tropical Diseases, 2015)
Cutaneous leishmaniasis caused by Leishmania major is an emergent, uncontrolled public health problem and there is no vaccine. A promising prophylactic approach has been immunotherapy with Toll-like receptor (TLR) agonists to enhance parasite-specific immune responses. We have previously reported that vaccination of C57BL/6 mice with live L. major plus the TLR9 agonist CpG DNA prevents lesion development and confers immunity to reinfection. Our current study aims to investigate whether other TLR agonists can be used in leishmanization without induction of lesion formation. We found that live L. major plus the TLR2 agonist Pam3CSK4 reduced the pathology in both genetically resistant (C57BL/6) and susceptible (BALB/c) mouse strains. The addition of Pam3CSK4 activated dermal dendritic cells and macrophages to produce greater amounts of proinflammatory cytokines in both mouse strains. Both Th1 and Th17 responses were enhanced by leishmanization with L. major plus Pam3CSK4 in C57BL/6 mice; however, Th17 cells were unchanged in BALB/c mice. The production of IL-17 from neutrophils was enhanced in both strains infected with L. major plus Pam3CSK4. However, the sustained influx of neutrophils in sites of infection was only observed in BALB/c mice. Our data demonstrate that the mechanism behind leishmanization with TLR agonists may be very different depending upon the immunological background of the host. This needs to be taken into account for the rational development of successful vaccines against the disease.